Analysis of firearm deaths from Central Delhi region - A 6-year retrospective study - Kumar, Raj; Buchade, Dhiraj; Bhart , Rohit; Kishore, Upender (Journal of Indian Academy of Forensic Medicine, 2021)
Firearm injuries were well known for their atypical findings and appearances in routine so a retrospective study from 2013 to 2018  was performed to evaluate the morphology of firearm injuries and the damaged caused by it. Data of 65 cases was collected from post  mortem notes of the deceased. It was observed that the age group of 21-40 years was most commonly affected with 63 cases (96.9%)  and a male : female ratio 31.5:1. Individuals of the Hinduism religion (50 cases, 76.9%) were most commonly affected and most of  the victims were brought dead or were dead on the spot (34 cases, 52.3%). Rifled firearm weapon most commonly used (63 cases,  96.9%) while shotgun was used in 02 cases (3.1%). Single entry (43 cases, 66.2%) and exit wounds 37 cases (56.9%) were most  commonly observed. In 41 cases (63.1%) no bullet was recovered while single bullet was recovered in 16 cases (24.6%) during post  mortem examination. Entry wounds were most commonly found on head, face and neck region of body in 29 cases (44.6%) followed  by chest region in 26 cases (40.0%), while right lower limb region with one case (1.5%) was least commonly found. Exit wounds  were most commonly found on head, face and neck region (22 cases, 33.8%) followed by back region (15 cases, 23.1%). Lungs (22  cases, 33.8%) and brain (21 cases, 32.3%) were most commonly damaged organs in firearm injuries while kidneys and spleen (2  cases, 3.1%) each were least commonly involved organs. Skull and facial bones (23 cases, 35.4%) were most commonly fractured  bones by firearm weapons followed by ribs and clavicle (17 cases, 26.2%). Abrasion collar was the most common entry wound  artefact (53 cases, 81.5%) followed by smudging/ blackening/ stippling (20 cases, 30.8%). Homicidal was the most common manner  of death with 44 cases (67.7%), followed by Suicidal with 15 cases (23.1%). Shock and Haemorrhage was the most common cause of  death with 30 cases (46.2%).
Keywords: Firearm injuries; Entry wound; Exit Wound; Rifled firearm; Shotgun firearm; Cause of death